Synthesis of determined system reconstracting the given random sequence - Matviychuk, Yaroslav (Overseas Publishers Associa, 1999)
A synthesis method for the ordinary differential equations is proposed. Their solutions reconstruct the statistical properties of the given pseudo-random sequence. The method is illustrated by an example of simulating singular Lorenz attractor and the sequence of pseudo-random numbers whish are uniformly distributed within [0,1] interval.
Синтез детермінованих систем, що відтворюють задані випадкові послідовності
Keywords: mathematical simulation; identification; strange attractor; random processes